Biphasic 2-methyltetrahydrofuran/oxalic acid/water pretreatment to enhance cellulose enzymatic hydrolysis and lignin valorization. (November 2017) - Li, Shu-Xian; Li, Ming-Fei; Bian, Jing; Sun, Shao-Ni; Peng, Feng; Xue, Zhi-Min
Graphical abstract: Highlights: Lignocellulose was pretreated by biphasic 2-MeTHF/oxalic acid/water system. Cellulose conversion rate was enhanced by 6.7-fold during enzymatic hydrolysis. The lignin obtained had a very low amount of contaminated sugars (0.67–2.39%). The lignin exhibited representative structure (such as β-O-4, β-β linkages). Abstract: A biphasic pretreatment was adopted to disturb the recalcitrant structure of bamboo for further enzymatic hydrolysis and to obtain easily valorized lignin by-product. The biphasic system consisted of biomass-derived chemicals—2-methyltetrahydrofuran and oxalic acid as well as water, and the reactions were conducted at 120–180 °C for 20 min. The treatment resulted in notable removal of hemicelluloses and lignin. After the pretreatment, the cellulose conversion rate during enzymatic hydrolysis was enhanced by 6.7-fold as compared to the unpretreated raw material. Comprehensive analysis of the lignin product indicated that it exhibited representative structure (such as β-O-4, β-β linkages) as compared to native lignin, contained a very low amount of contaminated sugars (0.67–2.39%), and had a relatively medium molecular weight (Mw 2240–3730 g/mol) and good solubility in many organic solvents. This indicated that the lignin showed great potential application in conversion into materials and liquid fuels.